Sistem Pendukung Keputusan Penentuan Jasa Ekspedisi Terbaik Menerapkan Metode ARAS - Nova Saragih; Agung Triayudi; Mesran Mesran (Jurnal Sistem Komputer dan Informatika (JSON), 2023)
The increase in users of goods delivery services throughout Indonesia has resulted in more and more new companies in this field. Consumers also believe in using their services in sending their goods delivered using goods delivery services. The large number of companies that run the goods delivery service business, makes users confused in shipping goods to consumers. There are factors that influence the freight forwarding company's services to be known by the public and the level of promotion from each expeditionary party so that people are confident in using the freight forwarding services. In determining the best expedition services in the city of Medan there are several criteria, namely service, experience, responsiveness, cost and age. Based on these problems, a decision support system is needed as a problem solving technique and is assisted by a method that can produce an accurate final value. The method is the Additive Ratio Assessment (ARAS) method in which the method is very helpful in producing the best weight and preference values from alternative data and criteria so that the final result is to determine the best expedition services in the city of Medan in Alternative A14 with a value of 1.0000, namely expedition services TNT.